The Relationship between Students’ Understanding of Pancasila Educational Values and Their Attitudes toward the Rejection of Online Gambling (A Study of Students at Universitas Budi Darma) - Sumiaty Adelina Hutabarat; Norenta Sitohang (Literacy: Journal of Education and Social Science, 2025)
This study aims to analyze the relationship between students’ understanding of the values taught in the Pancasila Education course and their attitudes toward rejecting online gambling practices. The increasing access to digital technology has encouraged various forms of misuse, including online gambling, which has the potential to damage students’ academic, economic, and moral aspects. Pancasila Education is viewed as a strategic instrument in shaping students’ character, integrity, and legal awareness. This study employs a quantitative approach with an explanatory research design. The sample consists of 24 students who have completed the Pancasila Education course. Data were collected using a Likert-scale questionnaire with 20 statement items. The validity test results indicate that all items meet the validity criteria, while the reliability test yields a Cronbach’s Alpha value of 0.916, indicating a very high level of consistency. Simple regression analysis shows a significant relationship between students’ understanding of Pancasila values and their anti–online gambling attitudes (t = 5.28; p < 0.05), with a coefficient of determination of 0.568. These findings indicate that the higher students’ understanding of Pancasila values, the stronger their tendency to reject online gambling practices. The results provide important implications for strengthening character education in higher education in response to the challenges of the digital era.